Different Causes and its Association in Children with Cerebral Palsy - Akkad Rafique, Kamran Saeed, Mehtab Ali, Tauseef Ahmed Baluch, Hafiz Ahmed Fayyaz Bajwa, Syed Faraz Ul Hassan Shah Gillani, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the different causes and their association of cerebral palsy in children. Methods: We conducted this cross-sectional survey using consecutive sampling technique at the orthopedic surgery department Mayo hospital, Lahore from October 2011 to November. The sample size was 200 children of all age groups, on history and clinical examination who were diagnosed with cerebral palsy were included in the study and children or their parents refused to participate in the study were excluded. Results: Out of the total 200 children, 42(21%) had <1year of age, 80(40%) has 1-5 year age, 62(31%) has 5-15 year and 16(8%) had reached the skeletal maturity. Majority, 130(65%) were boy and 70(35%) were girls. None of the participant was married till study completion. When education status was asked, majority 127(63.5%) were illiterate and 28(14%) children were admitted in nursery, 27(13.5%) had primary education, 13(6.5%) completed the matriculation and only 5(2.5%) children were enrolled as undergraduate. Conclusion: Low socioeconomic status and illiterate population were in majority. Most children had age up to five years with one third of the children had associated illness. Keywords: Cerebral palsy, congenital disease, central nervous system, motor impairment syndrome, gait analysis.